2022
DOI: 10.3390/ijerph19074301
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption on the Heaviest Drinking Occasion and Hangovers during the First Dutch COVID-19 Lockdown

Abstract: The purpose of this study was to compare alcohol consumption between the heaviest drinking occasion in the period before the coronavirus disease 2019 (COVID-19) lockdown (15 January–14 March 2020) and the first COVID-19 lockdown period (15 March–11 May 2020) in the Netherlands, including the presence and severity of associated hangovers. The analysis included a sub-sample from the “Corona Lockdown: how fit are you?” (CLOFIT) study, comprising N = 761 participants who reported consuming alcohol in 2020. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…That said, this increase in alcohol sales also did not translate to an increase in binge drinking, with no statistically significant change in the days per month of binge drinking or the maximum drinks per day. Previous literature on changes in binge drinking with the pandemic yielded mixed results, with studies reporting lower frequencies of binge drinking in a first-year college student cohort, and two separate cohorts in Japan and the Netherlands after the start of the pandemic ( Bonar et al., 2021 , Merlo et al., 2022 ; Stickley, Shirama, Inagawa, & Sumiyoshi, 2022 ). Conversely, hazardous drinking was elevated in Hubei at the epicenter of the pandemic in March 2020 relative to less affected areas of China at that time ( Ahmed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…That said, this increase in alcohol sales also did not translate to an increase in binge drinking, with no statistically significant change in the days per month of binge drinking or the maximum drinks per day. Previous literature on changes in binge drinking with the pandemic yielded mixed results, with studies reporting lower frequencies of binge drinking in a first-year college student cohort, and two separate cohorts in Japan and the Netherlands after the start of the pandemic ( Bonar et al., 2021 , Merlo et al., 2022 ; Stickley, Shirama, Inagawa, & Sumiyoshi, 2022 ). Conversely, hazardous drinking was elevated in Hubei at the epicenter of the pandemic in March 2020 relative to less affected areas of China at that time ( Ahmed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals can influence lifestyle factors to improve their immune fitness and thus their pandemic preparedness. For example, research has shown a significant correlation between alcohol consumption and perceived immune fitness [ 53 , 54 , 55 ]. In the same subjects, a significant correlation was also observed between perceived immune fitness and the presence and severity of COVID-19 symptoms [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown a significant correlation between alcohol consumption and perceived immune fitness [ 53 , 54 , 55 ]. In the same subjects, a significant correlation was also observed between perceived immune fitness and the presence and severity of COVID-19 symptoms [ 53 , 54 , 55 ]. Reducing alcohol consumption can thus help to improve the perceived immune fitness.…”
Section: Discussionmentioning
confidence: 99%
“…A third analysis examined alcohol consumption and hangovers on the heaviest drinking occasion before and during the first COVID-19 lockdown [24]. For young adults (18 to Proceedings 2022, 80, 5 5 of 7 35 years old), but not the older age groups, there was a significant reduction in the number of alcoholic drinks consumed on the heaviest drinking occasion during lockdown, as compared to before the lockdown.…”
Section: Impact Of Covid-19mentioning
confidence: 99%